Russian prefixal posture verbs as a means of spatial thinking verbalization - A.V. Trofimova; V.A. Kosova (Ученые записки Казанского университета: Серия Гуманитарные науки)
The semantics of Russian posture verbs has been studied. The analysis covers derivative words formed on the basis of the prefixes v- (в- 'in'), na- (на- 'on'), pod- (под- 'under'), nad- (над- 'above'), pred- (пред- 'in front of'), za- (за- 'behind') and verbs of position in space, such as lezhat' (лежать 'lie'), sidet' (сидеть 'sit'), stoyat' (стоять 'stand'), viset' (висеть 'hang'). Appealing to these lexical items within the frame of compound semantics is determined by the following fact: they are indicative of the features of human spatial perception that developed in high antiquity. Based on the results of the analysis, five groups of derivative words have been distinguished. The first group includes prefixal verbs which save posture and spatial semantics. But all of them are archaisms now. Posture verbs that denote the end of action belong to the second group. Other derivative words often expand their meaning through neutralization of the seme that implies the posture. Existential verbs with modal component form the third group. Verbs of speech and social activity constitute the fourth group. Finally, posture verbs with complicated additional semes are included the sixth group. At the same time, the verbal postural semantics and prefixal spatial semantics can be restored even in figurative meanings. It has been concluded that the prefixes of posture verbs in the modern Russian language lost their spatial meaning, which used to be inherent. This is due to the development of bounded prefixal meaning that failed to comply with the stative semantics of the posture verb.